Design, Optimization, and Evaluation of Capecitabine-loaded Chitosan Microspheres for Colon Targeting - Jena, Goutam Kumar (Asian Journal of Pharmaceutics (AJP), 2017)
Aims: Capecitabine is an orally-administered chemotherapeutic agent used in the treatment of advanced stage of colorectal cancers (CRC). The present research was to formulate and optimize capecitabine-loaded microspheres for CRC targeting to enhance bioavailability, reduce dose, minimize side effect, and sustain drug release for 24 h. Materials and Methods: Capecitabine-loaded microspheres were prepared by emulsion solvent evaporation method. Nine formulations of microspheres with different ratios of capecitabine and chitosan were prepared. A central composite design with design expert software version 10.0.3.1 was employed in formulating and optimizing the microspheres to maximize entrapment efficiency and minimize particle size. The optimized microspheres were coated with Eudragit S100, a pH sensitive polymer and were evaluated. Results and Discussion: Fourier transform infrared spectroscopy study revealed the compatibility of drug with excipients while differential scanning calorimetry study confirmed the complete drug entrapment in polymer matrix and scanning electron microscopy revealed spherical shape of microspheres. The release profile of capecitabine from Eudragit S100-coated chitosan microspheres was found to be pH dependent. In vitro dissolution studies of Eudragit S100-coated microspheres revealed negligible released in simulated gastric as well as intestinal fluid, followed by 100% released in simulated colonic fluid, in 24 h. The optimized microspheres showed colon-specific controlled release properties, and thus could be effective for CRC treatment. Conclusion: Capecitabine-loaded microspheres can be prepared using chitosan and Eudragit S100 as sustained release with mucoadhesion and pH sensitive polymer, respectively, for CRC targeting.